The effects of acute exercise and glutamine supplementation on the immune system of female athletes - Alijani, E; Hosseini, Z. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study is to investigate the effects of 2 hours acute and exhaustive exercise and glutamine supplementation on immune system of female student athletes. The question therefore arises as to whether extra glutamine should be provided after acute and exhaustive exercise. On the base of findings of this study , it is noted that 2hrs acute and exhaustive exercise can alter white blood cells and subsets. As indicated in this study , glutamine may be concerned as an important supplement for the immune system in order to reduce the effects of prolonged and exhaustive exercise on white blood cells and subsets . Due to our findings which are in agreement with many other results [2,4,8,9,10,12,13] it is concluded that provision of glutamine might be beneficial for female student athletes at particular times during their training in order to minimize the probable exercise- induced effects.